2013
DOI: 10.1007/s00595-013-0805-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective non-randomized comparison of open versus laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair under different anesthetic methods

Abstract: Transabdominal preperitoneal repair under spinal anesthesia proved superior to open repair performed under different types of anesthesia in terms of immediate (24-h) postoperative pain. The method of anesthesia might have contributed more to this favorable outcome than the surgical technique itself, but at the cost of a high urinary retention incidence. The incidence of chronic pain was lower after TAPP repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
2
19
0
2
Order By: Relevance
“…An objective evaluation of chronic pain is difficult, partly because there is no definition of chronic pain for VIHR, which is in contrast to inguinal hernia repair, in which chronic pain is defined as pain lasting over 6 months postoperatively in the International Guidelines of Chronic Pain for Inguinal Hernias [50]. The recent literature [11,12,51] using this definition described the incidence of chronic pain after sIPOM to be in the range of 1.3-14.7 %, which was much higher than that after laparoscopic inguinal hernia repair [52,53]. Therefore, the postoperative pain of IPOM-Plus and sIPOM should be evaluated and compared.…”
Section: Chronic Painmentioning
confidence: 81%
“…An objective evaluation of chronic pain is difficult, partly because there is no definition of chronic pain for VIHR, which is in contrast to inguinal hernia repair, in which chronic pain is defined as pain lasting over 6 months postoperatively in the International Guidelines of Chronic Pain for Inguinal Hernias [50]. The recent literature [11,12,51] using this definition described the incidence of chronic pain after sIPOM to be in the range of 1.3-14.7 %, which was much higher than that after laparoscopic inguinal hernia repair [52,53]. Therefore, the postoperative pain of IPOM-Plus and sIPOM should be evaluated and compared.…”
Section: Chronic Painmentioning
confidence: 81%
“…The EU Hernia Trialists Collaboration has stated in several reports that greater chronic postoperative pain occurs after AA than after TAPP, although none of these reports provide information about early postoperative pain 9) . The reports by Symeonidis et al 4) and Mahon et al 5) are representative of early postoperative pain reports, although there are a few other reports stating that there is less postoperative pain after AA than TAPP, based on the result of the frequency of analgesic use, Visual Analogue Scale (VAS), and the number of days required for rehabilitation into society. Certainly, it is highly likely that the frequency of use of analgesics and the number of days taken to reintegrate are directly related to the pain experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to AA, postoperative pain after TAPP is usually reported to be less intense 4)5) ; however, there was no comparative study about the current perception threshold (CPT) between the two surgical techniques. Scale Severity of pain 1 No pain on coughing or sneezing 2 No pain on movement, but pain on coughing or sneezing 3 No pain at rest, but pain on movement 4 Cannot sleep without pain killer…”
Section: Introductionmentioning
confidence: 99%
“…It also facilitates faster mobilization and earlier discharge/fulfillment of discharge criteria from post anesthetic care units than other anesthetic techniques [11,12]. On the other hand, in a very recent prospective non-randomized study, Symeonidis and colleagues reported that transabdominal preperitoneal repair under spinal anesthesia was superior to open repair performed under different types of anesthesia in terms of immediate postoperative (24-h) pain [13]. However, repairs with spinal anesthesia resulted in a higher rate of urinary retention which could be eliminated by LA.…”
mentioning
confidence: 99%